Structural analysis of human platelet membrane glycoprotein I complex. - Nachman, R L (Proc Natl Acad Sci U S A, 1979)
The glycoprotein I complex, consisting of two polypeptides of Mr 210,000 and 150,000, was isolated from human platelet membranes by wheat germ lectin affinity chromatography. Glycocalicin, a soluble loosely bound membrane glycoprotein of Mr 150,000 related to the glycoprotein I system, was also purified. The isolated polypeptides were radioiodinated in sodium dodecyl sulfate/polyacrylamide gels and digested with trypsin, and the labeled peptide digest was analyzed by two-dimensional high-voltage electrophoresis and thin-layer chromatography. The two polypeptides of Mr 210,000 and 150,000 in the glycoprotein I complex had essentially identical radioactive peptide maps. Glycocalicin had a completely different tryptic peptide map. These studies shed light on the molecular relationships of some of the components of the platelet membrane glycoprotein I system. The possibility is raised that the receptorlike function of the intrinsic platelet membrane glycoproteins may be related to the polymeric subunit associations of the constituent polypeptides. IMAGES: